PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MOTIVASI BELAJAR SISWA DITINJAU DARI PERBEDAAN JENIS KELAMIN PADA MATA PELAJARAN IPS KELAS VIII DI SMPN 4 PEKANBARU - Siti Komariyah; Sumarno Sumarno; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of teacher pedagogical competencies on student learning motivation in terms of gender differences in social studies in class VIII. This research was carried out at Junior High School 4 Pekanbaru. The population in this study was class VIII students at Junior High School 4 Pekanbaru. The population is 332 students. With the propotional random sampling technique obtained a sample of 181 students consisting of 87 men and 94 women. Data were obtained through questionnaire instruments for pedagogical competence data of teachers and data on student motivation. The data obtained are then analyzed by simple linear regression analysis and different tests (independent t test). The results showed that the teacher's pedagogical competence had a positive effect on student learning motivation at 0.715. The learning motivation of male students is higher than the learning motivation of female students. This is evidenced by the average yield of 81.0575 for male student motivation and 76.0213 for female student motivation. Key Words: Teacher Pedagogic Competence, Student Learning Motivation, Gender